2014
DOI: 10.1007/s11999-013-2997-4
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific Guides Do Not Improve Accuracy in Total Knee Arthroplasty: A Prospective Randomized Controlled Trial

Abstract: Background Recently, patient-specific guides (PSGs) have been introduced, claiming a significant improvement in accuracy and reproducibility of component positioning in TKA. Despite intensive marketing by the manufacturers, this claim has not yet been confirmed in a controlled prospective trial. Questions/purposes We (1) compared three-planar component alignment and overall coronal mechanical alignment between PSG and conventional instrumentation and (2) logged the need for applying changes in the suggested po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
202
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(215 citation statements)
references
References 36 publications
11
202
2
Order By: Relevance
“…Pfitzner et al reported similar findings, with tibial component alignment of 1.0°, with a 3% outlier (±3°from neutral) rate, and femoral component alignment of 1.0°, with a 3% outlier (±3°from [32,42]. Some of the variability in results may relate to particular surgical methods or to the reference standard used to assess error.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Pfitzner et al reported similar findings, with tibial component alignment of 1.0°, with a 3% outlier (±3°from neutral) rate, and femoral component alignment of 1.0°, with a 3% outlier (±3°from [32,42]. Some of the variability in results may relate to particular surgical methods or to the reference standard used to assess error.…”
Section: Discussionmentioning
confidence: 78%
“…For example, in the present study, the entire femoral preparation was completed first in order to optimize placement of the tibial cutting guide. Further, some studies used postoperative imaging as the reference standard [34], while others used intra-operative assessments based on computer-assisted navigation instruments [21,32,42]. In the sagittal plane, the KA2 group achieved an average slope closer to 3°of posterior slope (2.7°) compared to the VISIONAIRE group (4.4°).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study was designed to verify the utility of CT-based Signature™ PSI for precise implant positioning. In general, results of studies on PSI are equivocal [8,15,[25][26][27][28]. We believe that results obtained with one particular PSI system are not automatically applicable to other systems and should not be generalised [14,23].…”
Section: Discussionmentioning
confidence: 94%
“…Particular systems differ in terms of shape and contact areas between the guide and bone. Finally, there are magnetic resonance imaging (MRI)-and CT-based custom guides available [17], and in some systems, pre-operative standing AP X-ray of the entire leg is required to fabricate PSI [26]. In the Signature™ system, which was the subject of this paper, pinning guides are used to restore mechanical axis, and both MRI and CT scans may be used.…”
Section: Discussionmentioning
confidence: 99%